2020
DOI: 10.1101/2020.03.04.976688
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thalamic activity patterns unfolding over multiple time scales predict seizure onset in absence epilepsy

Abstract: The brain has a remarkable, yet poorly understood, capacity to perform rapid dynamic switching between different cognitive states. Absence epilepsy, characterized by sudden transitions to and from highly synchronous thalamocortical oscillations, provides a unique window to investigate rapid state switching. Here we explored the transition into seizures in detail using simultaneous extracellular unit recordings from the thalamocortical circuit in the Scn8a mouse, a validated murine model of absence epilepsy. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…Our work provides the first insight of PO neuronal firing during SWDs in a freely moving GAERS. Sorokin et al (2020) recorded from a mouse model of ASs and observed a ramp in PO firing preceding the onset, but this feature was variable and not observed here. However, overall firing rates were similar and alike Sorokin et al (2020), a reduction in firing, followed by a sharp increase was observed just prior to SWD onset.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Our work provides the first insight of PO neuronal firing during SWDs in a freely moving GAERS. Sorokin et al (2020) recorded from a mouse model of ASs and observed a ramp in PO firing preceding the onset, but this feature was variable and not observed here. However, overall firing rates were similar and alike Sorokin et al (2020), a reduction in firing, followed by a sharp increase was observed just prior to SWD onset.…”
Section: Discussionmentioning
confidence: 54%
“…Sorokin et al (2020) recorded from a mouse model of ASs and observed a ramp in PO firing preceding the onset, but this feature was variable and not observed here. However, overall firing rates were similar and alike Sorokin et al (2020), a reduction in firing, followed by a sharp increase was observed just prior to SWD onset. Our work provides a major step forward to these results since we show that these dynamics represent an underlying shift from tonic to burst firing in the PO neuronal population.…”
Section: Discussionmentioning
confidence: 54%